Production and characterisation of a SARS-CoV-2 S-protein RBD homodimer with increased avidity for specific antibodies - A. A. Derkaev; E. I. Ryabova; V. V. Prokofiev; I. A. Favorskaya; D. M. Grousova; I. B. Esmagambetov; I. V. Dolzhikova; D. V. Shcheblyakov (Биопрепараты: Профилактика, диагностика, лечение)
Monitoring of the proportion of immune individuals and the effectiveness of vaccination in a population involves evaluation of several important parameters, including the level of virus-neutralising antibodies. In order to combat the COVID-19 pandemic, it is essential to develop approaches to detecting SARS-CoV-2 neutralising antibodies by safe, simple and rapid methods that do not require live viruses. To develop a test system for enzyme-linked immunosorbent assay (ELISA) that detects potential neutralising antibodies, it is necessary to obtain a highly purified recombinant receptor-binding domain (RBD) of the spike (S) protein with high avidity for specific antibodies.The aim of the study was to obtain and characterise a SARS-CoV-2 S-protein RBD homodimer and a recombinant RBD-expressing cell line, as well as to create an ELISA system for detecting potential neutralising antibodies.Materials and methods: the genetic construct was designed in silico. To generate a stable producer cell line, the authors transfected CHO-S cells, subjected them to antibiotic pressure, and selected the optimal clone. To isolate monomeric and homodimeric RBD forms, the authors purified the recombinant RBD by chromatographic methods. Further, they analysed the activity of the RBD forms by Western blotting, bio-layer interferometry, and indirect ELISA. The analysis involved mono clonal antibodies GamXRH19, GamP2C5, and h6g3, as well as serum samples from volunteers vaccinated with Gam-COVID-Vac (Sputnik V) and unvaccinated ones.Results: the authors produced the CHO-S cell line for stable expression of the recombinant SARS-CoV-2 S-protein RBD. The study demonstrated the recombinant RBD’s ability to homodimerise after fed-batch cultivation of the cell line for more than 7 days due to the presence of unpaired cysteines. The purified recombinant RBD yield from culture broth was 30–50 mg/L. Monomeric and homodimeric RBD forms were separated using gel-filtration chromatography and characterised by their ability to interact with specific monoclonal antibodies, as well as with serum samples from vaccinated volunteers. The homodimeric recombinant RBD showed increased avidity for both monoclonal and immune sera antibodies.Conclusions: the homodimeric recombinant RBD may be more preferable for the analysis of levels of antibodies to the receptor-binding domain of the SARS-CoV-2 S protein.